Transformational processes in post-technogenic ecosystems of Kolomyia lignite and Yaziv sulfur deposits in Western Ukraine - Henyk, Yaroslav; Popovych, Vasyl; Zayachuk, Vasyl; Dyda, Oleksandra; Gociy, Nataliya; Bosak, Pavlo (Ecological Questions, 2023)
Restoration of post-tech ecosystems of the Western region of Ukraine takes place both through natural self-overgrowth with vegetation and through the implementation of phytomeliorative measures - artificial afforestation of disturbed areas. These processes have been studied on post-technogenic territories of Kolomyia lignite and Yaziv sulfur deposits. Transformational processes in the study area are caused mainly by three factors: natural succession of vegetation (from the emergence of mosses and pioneering species of grasses and trees to the formation of stable plant communities); human economic activity (phytomeliorative measures for sowing grasses and creating forest crops) and cattle grazing (appearance of fruit tree species in phytocenoses). Transformational processes in edaphotopes are primarily determined by two factors - the natural succession of vegetation and erosion processes. Due to the long process of restoration of disturbed ecosystems in post-man-made areas, relatively complex and rich in species composition stable plant communities are gradually formed, which contribute to the formation of embriozems, identification of soil genetic horizons, increasing the thickness of the soil profile and approximating the physical and mechanical properties of the upper layers of the soil to the properties of natural zonal soils. The species composition and structure of vegetation in the post-technogenic territories of Kolomyia lignite and Yaziv sulfur deposits of the Western region of Ukraine have been determined. The study showed that the dendroflora of post-technological areas is represented by 59 species of tree plants.Changes in the components of phytocenoses and edaphotopes are presented and the factors of transformation processes in disturbed ecosystems are analyzed. Stages of natural succession of vegetation in post-technogenic territories of lignite and sulfur deposits have been established. Physico-chemical properties of the formed embriozems were analyzed and their comparative analysis with zonal soils was carried out. It is established that the processes of vegetation restoration and soil formation in post-technogenic territories cause the gradual formation of complex plant groups and relatively stable and stable natural ecosystems.